The metabolite ILA of Akkermansia muciniphila improves AP-related intestinal injury by targeting and inhibiting CASP3 activity - Li, Peiyu; Yu, Jiuliang; Li, Tao; Gong, Xiaoyong; Li, Le; Cui, Yi; He, Jiayi; Li, Bo; Wu, Shuqi; Guan, Qingyang; Zhang, Zhiming; Dai, Xingui; et al. (Frontiers in Microbiology, 2025)
ObjectiveAcute Pancreatitis (AP) is a common acute abdominal disease in clinical practice. The gut microbiome is recognized as a key regulator in the development of acute pancreatitis. Akkermansia muciniphila (AKK) is recognized as a functional probiotic strain and has a beneficial effect on the progression of many diseases. However, the role of the AKK in the development of AP remains unclear. Here, we evaluated the potential contribution of AKK to AP.DesignRelative abundance of gut microbial AKK in AP was evaluated. A rat model of acute pancreatitis was established by retrograde pancreatic duct infusion of sodium taurocholate. Non-targeted and targeted metabolomics analysis were used for metabolites analysis.ResultsWe first found that the relative abundance of gut microbial AKK in AP patients was significantly reduced compared with that in healthy subjects. Live AKK supplementation, as well as supplementation with its culture supernatant, remarkably alleviates AP-related intestinal injury in AP rat models. Metabolomics studies found that the live AKK was able to generate Indole-3-lactic acid (ILA). ILA exerted a protective effect against AP-related intestinal injury, and significantly reduce inflammatory cell activation and pro-inflammatory factor overproduction. The mechanistic study revealed that ILA inhibits the apoptosis of intestinal epithelial cells by suppressing the activity of CASP3, and improves the role of intestinal barrier dysfunction in the AP model.ConclusionWe revealed that ILA, derived from live AKK, may act as a novel endogenous agonist for CASP3. ILA may serve as a new potential treatment method for intestinal injury in AP after successfully translating its efficacy into clinical practice.